2021
DOI: 10.2196/22619
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telehealth Services to Assess, Monitor, and Treat Neurodevelopmental Disorders: Systematic Review

Abstract: Background In response to COVID-19, there has been increasing momentum in telehealth development and delivery. To assess the anticipated exponential growth in telehealth, it is important to accurately capture how telehealth has been used in specific mental health fields prior to the pandemic. Objective This systematic review aimed to highlight how telehealth has been used with clinical samples in the neurodevelopmental field, including patients with neurodevelopmental d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 63 publications
(89 reference statements)
0
33
0
2
Order By: Relevance
“…Tele-assessments have been identified as effective in the diagnosing and management of neurodevelopmental disorders, including ADHD [37] , [38] , but less is known about the accuracy of these assessments for adults compared with face-to-face assessments [37] .…”
Section: Resultsmentioning
confidence: 99%
“…Tele-assessments have been identified as effective in the diagnosing and management of neurodevelopmental disorders, including ADHD [37] , [38] , but less is known about the accuracy of these assessments for adults compared with face-to-face assessments [37] .…”
Section: Resultsmentioning
confidence: 99%
“… Sutherland, Trembath, and Roberts (2018) conducted a systematic review of telehealth provision for autism services for children and adults and found that outcomes were largely positive and equivalent to those achieved via face-to-face services. However, the majority of research has been focused on delivery of therapy rather than diagnostic assessments ( Valentine et al, 2021 ). The use of telehealth for autism diagnoses has been investigated in three studies.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of telepractice are well‐documented across both education and allied health (Keck and Doarn 2014, Valentine et al . 2021). These benefits include increased service availability, convenience, improved caseload management resulting in more cost‐effective service delivery, improved access to services for people living in rural and remote areas (Fairweather et al .…”
Section: Introductionmentioning
confidence: 99%